Physiological characteristics of phytoplankton in response to different light environments in the Philippine Sea, Northwestern Pacific Ocean - Lee, Chang Hwa; Kang, Jae Joong; Min, Jun-Oh; Bae, Hyeonji; Kim, Yejin; Park, Sanghoon; Kim, Joonmin; Kim, Dongseon; Lee, Sang Heon (Frontiers in Marine Science, 2022)
The physiological status of phytoplankton, used to determine the quantity and quality of basic food sources in marine ecosystems, can change rapidly due to ambient environmental conditions (e.g., light, temperature, and nutrients). To understand the physiological characteristics of phytoplankton, the phytoplankton community composition, pigment concentration, primary production, and pigment production rate were estimated at 100% and 1% light depths in the Philippine Sea during the summer of 2019. The predominant phytoplankton classes at both light depths were Prochlorococcus and Synechococcus during the study period. Pigment concentrations, except for photoprotective pigment concentrations (i.e., diadinoxanthin and zeaxanthin), were significantly higher (t-test, p<0.05) at 1% light depth to increase the light-harvesting efficiency. The production rates of these pigments had a weak correlation with primary production at 100% light depth, whereas they showed a strong positive relationship at 1% light depth. Moreover, all photosynthetic pigments had a significantly faster turnover rate at 100% light depth compared with 1% light depth to obtain light energy to repair PSII subunits damaged by strong light. This suggests that the phytoplankton community, especially cyanobacteria (Prochlorococcus and Synechococcus), could use light energy absorbed by newly produced photosynthetic pigments for repairing photoinhibition-damaged PSII as well as for production activity. A further study on photosynthetic pigments responding to light conditions must be conducted for a better understanding of the physiological conditions of phytoplankton.